How does climate exacerbate root causes of conflict in Ethiopia? Climate Security Pathway Analysis - Sax, Niklas; Hassan, Gamal Mohamed; Abdi, Abdimajid Nunow; Ferré Garcia, Tània; Madurga Lopez, Ignacio M.; Carneiro, Bia; Liebig, Theresa Ines; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR FOCUS Climate Security, 2023)
"This factsheet gives answers on how climate exacerbates root causes of conflict in Sudan, using an impact pathway analysis. Two main impact pathways are identified: 1. Resource Access and Availability: Climate variability and extreme events are depleting Ethiopia’s land and water resources, exacerbating resource-based conflicts. Resource conflicts over land are often the basis for ethnic violence between communities competing for territory and power in the Ethiopian federal system. 2. Livelihood and Food Security: Most of Ethiopia’s land is vulnerable to climate extremes that affect food availability. Local food insecurity hotspots in Tigray, Somali, and Afar correlate with higher conflict frequency, making them vulnerable to climate security risks."